Khasiat fluralaner terhadap kutu keras (Rhipicephalus sanguineus) pada anjing - Upik Kesumawati Hadi; Susi Soviana; Azery Bin Kamiring; Syarif Hidayat (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2020)
Fluralaner is a new molecular entity from the isoxazoline class that exhibits acaricidal and insecticidal activity and it is recommended as an anti-ticks drugs. The aim of this study is to analyze the effect of fluralaner against dog infested by tick. A total of 10 dogs weighing about 20-40 kg which consists of various races, were divided into control groups with-out medication (n=2), and treatment group (n=8) received fluralaner tablets once by orally, at a dose of 25 mg / kg body weight. The results showed that based on observation of day of drug application at 24th hour was the time where the drug reaches the standard of efficacy with decrease number of the tick by 97.3%. In 28 and 56 days post treatment were the highest levels of efficacy with a decrease number of tick reaching 100%. The efficacy of the fluralaner was still very high until 84 days post treatment reached up to 94.1%. This study also proved that 12 weeks of drug work believed to overcome reinfestation of the tick. The rapid tick-killing effect and the long duration of efficacy showed the potency fluralaner to aid in the prevention of tick borne diseases.